PENERAPAN MODEL PEMBELAJARAN DEBAT AKTIF UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PAI DI SMK KARTIKA GRATI KABUPATEN PASURUAN - Nur Hasan (JIE (Journal of Islamic Education), 2019)
In the activities of a country's education plays a very important role to ensure the survival of the country and nation because education is a vehicle to improve and raise the quality of human resources. Ba s sically education is an attempt to develop the pe rsonality and abilities of students towards maturity that will be able to stand on their own and pursue their goals. So that all needs can be achieved that need to be considered is the implementation of teaching which includes the selection of materials in accordance with the objectives, teaching methods and effective learning models in addition to evaluations to measure the quality of the success of the learning process that has been implemented . The method applied in this study is classroom action researc h packaged in a cycle, using the active debate method. Which is applied in SMK Kartika Grati, Pasuruan Regency, where in its application experiences activeness to students.